If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(9x + 2) + 8 + -16x = 0 Reorder the terms: 3(2 + 9x) + 8 + -16x = 0 (2 * 3 + 9x * 3) + 8 + -16x = 0 (6 + 27x) + 8 + -16x = 0 Reorder the terms: 6 + 8 + 27x + -16x = 0 Combine like terms: 6 + 8 = 14 14 + 27x + -16x = 0 Combine like terms: 27x + -16x = 11x 14 + 11x = 0 Solving 14 + 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 11x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 11x = 0 + -14 11x = 0 + -14 Combine like terms: 0 + -14 = -14 11x = -14 Divide each side by '11'. x = -1.272727273 Simplifying x = -1.272727273
| .5x+.1x=8 | | 6/12÷6/6 | | 5a^2-4ab+16b=0 | | 2.3=43.7 | | 4(6-2y)=64 | | 5a^2-4ab-16b=0 | | -6=x/9-7 | | 5/4x=9/4 | | 30+(4x+20)+(x+5)=180 | | 7(-9t+-9)+t= | | 3x-6-4x+9= | | 2+6n=18 | | 6n-12=96 | | 34c-13=55 | | 34c-13=15 | | 9tanx+2=7 | | W=3a-5n | | (2x-8)(x)=330 | | 20/(4-(10)) | | -22+2x=-8 | | 6r+29=83 | | 3x-6y=-3(30) | | C=F-32/1.8 | | Y=in(x+3) | | 8(4x+5y)=(5y*8)+4 | | 6+2x=5+7x | | 8h+7=127 | | 128=8y+2(x) | | 8+x+5=8+x+5 | | (2x+5)+(5x+3)+(7x+4)= | | x^2+2x+1=x-3 | | 8d-9-3d=31 |